Body composition during early infancy and developmental progression from 1 to 5 years of age: the Infant Anthropometry and Body Composition (iABC) cohort study among Ethiopian children. Issue 11 (17th May 2018) - Abera, Mubarek; Tesfaye, Markos; Admassu, Bitiya; Hanlon, Charlotte; Ritz, Christian; Wibaek, Rasmus; Michaelsen, Kim F.; Friis, Henrik; Wells, Jonathan C.; Andersen, Gregers S.; Girma, Tsinuel; Kæstel, Pernille
Abstract: Early nutrition and growth have been found to be important early exposures for later development. Studies of crude growth in terms of weight and length/height, however, cannot elucidate how body composition (BC) might mediate associations between nutrition and later development. In this study, we aimed to examine the relation between fat mass (FM) or fat-free mass (FFM) tissues at birth and their accretion during early infancy, and later developmental progression. In a birth cohort from Ethiopia, 455 children who have BC measurement at birth and 416 who have standardised rate of BC growth during infancy were followed up for outcome variable, and were included in the statistical analysis. The study sample was restricted to mothers living in Jimma town who gave birth to a term baby with a birth weight ≥1500 g and no evident congenital anomalies. The relationship between the exposure and outcome variables was examined using linear-mixed regression model. The finding revealed that FFM at birth was positively associated with global developmental progression from 1 to 5 years ( β =1·75; 95 % CI 0·11, 3·39) and from 4 to 5 years ( β =1·34; 95 % CI 0·23, 2·44) in the adjusted model. Furthermore, the rate of postnatal FFM tissue accretion was positively associated with development at 1 year of age ( β =0·50; 95 % CI 0·01, 0·99). Neither fetal nor postnatal FM showed a significant association. In conclusion, fetal, rather than postnatal, FFM tissue accretion was associated with developmental progression. Intervention studies are needed to assess whether nutrition interventions increasing FFM also increase cognitive development.